Metabolomic insights of cultured meat compared to conventional meat - Heejung Park; IHyeon Cho; Sojeong Heo; Kisoo Han; Young-jin Baek; Wan-sup Sim; Do-Won Jeong (Scientific Reports)
Abstract The growing global demand for sustainable food sources has accelerated the development of cultured meat as an alternative to traditional animal-based meat. Cultured meat is produced through advanced cell cultivation techniques, offering potential solutions to environmental, ethical, and food security challenges. This study aims to predict the safety of cultured meat compared to conventional chicken using a comprehensive metabolomics approach. We conducted a comparative analysis of conventional chicken meat, muscle satellite cells, and myotube formed cells. The findings reveal that while the overall metabolic profiles of cultured and conventional meats are largely comparable, significant differences exist in specific metabolites associated with nutrient metabolism. These variations suggest potential differences in the nutritional content of cultured meat, which could affect its dietary value. Despite these differences, our analysis indicates no significant impact on the safety of cultured meat, which remains within acceptable safety limits. This study contributes to the ongoing evaluation of cultured meat as a viable and safe alternative in the pursuit of sustainable food sources.